2012
DOI: 10.2147/ppa.s22495
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram for the management of major depressive disorder: a review of its efficacy, safety, and patient acceptability

Abstract: Escitalopram (escitalopram oxalate; Cipralex®, Lexapro®) is a selective serotonin reuptake inhibitor (SSRI) used for the treatment of major depressive disorder (MDD) and anxiety disorder. This drug exerts a highly selective, potent, and dose-dependent inhibitory effect on the human serotonin transport. By inhibiting the reuptake of serotonin into presynaptic nerve endings, this drug enhances the activity of serotonin in the central nervous system. Escitalopram also has allosteric activity. Moreover, the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 41 publications
5
49
0
5
Order By: Relevance
“…Escitalopram oxalate, also known as Cipralex Departments of 1 Pharmacy and antidepressants (11). The relevant results indicated that escitalopram oxalate was superior to a placebo, and almost as effective as, or superior to, other SSRIs, including citalopram, paroxetine, fluoxetine and sertraline, and serotonin-noradrenaline reuptake inhibitors, including duloxetine and sustained-release venlafaxine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Escitalopram oxalate, also known as Cipralex Departments of 1 Pharmacy and antidepressants (11). The relevant results indicated that escitalopram oxalate was superior to a placebo, and almost as effective as, or superior to, other SSRIs, including citalopram, paroxetine, fluoxetine and sertraline, and serotonin-noradrenaline reuptake inhibitors, including duloxetine and sustained-release venlafaxine.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant results indicated that escitalopram oxalate was superior to a placebo, and almost as effective as, or superior to, other SSRIs, including citalopram, paroxetine, fluoxetine and sertraline, and serotonin-noradrenaline reuptake inhibitors, including duloxetine and sustained-release venlafaxine. Escitalopram oxalate also exhibits favorable tolerability and causes generally mild and temporary adverse events (11). Since few studies of reports on the effects of escitalopram oxalate in NSCLC cells have been published, the present study attempts to examine the effects of escitalopram oxalate on NSCLC and the underlying mechanism involved.…”
Section: Introductionmentioning
confidence: 99%
“…Данные литературы об антигипертензивных эффектах СИОЗС немногочисленны и достаточно противоречивы [13,14]. Предполагается, что исполь-зование Эс может обеспечивать блокаду пресинапти-ческих серотониновых рецепторов, увеличивать выделение и накопление серотонина в синаптиче-ской щели, и, как результат, стабилизирует функцио-нирование серотонинергической системы [11].…”
Section: материал и методыunclassified
“…This activity inhibits serotonin (5-HT) reuptake and increases the amount of serotonin in synaptic clefts, which results in antidepressant action 2,3 .…”
Section: Introductionmentioning
confidence: 99%